2017
DOI: 10.1007/s11936-017-0513-y
|View full text |Cite
|
Sign up to set email alerts
|

Group A Streptococcus, Acute Rheumatic Fever and Rheumatic Heart Disease: Epidemiology and Clinical Considerations

Abstract: Opinion statementEarly recognition of group A streptococcal pharyngitis and appropriate management with benzathine penicillin using local clinical prediction rules together with validated rapi-strep testing when available should be incorporated in primary health care. A directed approach to the differential diagnosis of acute rheumatic fever now includes the concept of low-risk versus medium-to-high risk populations. Initiation of secondary prophylaxis and the establishment of early medium to long-term care pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
96
0
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 127 publications
(100 citation statements)
references
References 131 publications
0
96
0
4
Order By: Relevance
“…Finally, the subset used for the algorithm validation sub-study were selected opportunistically, which may have been open to selection bias. Despite these limitations, this study provides good baseline data for the prevalence of these common skin infections in a country where no other recent data exists and also provides valuable microbiological data on skin pathogens, which is lacking globally [1-3].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the subset used for the algorithm validation sub-study were selected opportunistically, which may have been open to selection bias. Despite these limitations, this study provides good baseline data for the prevalence of these common skin infections in a country where no other recent data exists and also provides valuable microbiological data on skin pathogens, which is lacking globally [1-3].…”
Section: Discussionmentioning
confidence: 99%
“…RHD is a largely preventable, acquired heart disease resulting from untreated or undertreated group A streptococcal infections in the community 18. A recent publication on the outcomes of women with rheumatic mitral disease, which largely excluded low-income countries, found that heart failure complicated 23% of women entering pregnancy with moderate or severe mitral regurgitation 13.…”
Section: Discussionmentioning
confidence: 99%
“…Streptococcus pyogenes is responsible for a wide range of illnesses, ranging from uncomplicated pharyngitis and impetigo to toxic shock syndrome and necrotizing fasciitis . Moreover, autoimmune sequelae such as acute rheumatic fever and rheumatic heart disease may arise after an inappropriately treated infection . Though not a severe illness, streptococcal pharyngitis is very common and associated with high costs .…”
mentioning
confidence: 99%